Parameters of Building Geometry that Affect Wind Flow With Regards to the Possibilities for their Implementation in Urban and Architectural Design in Poland - MOCHULSKA Mariya -Veronika; ZIELONKO-JUNG Katarzyna (Architecture, Civil Engineering, Environment)
In recent years, there has been a surge in Computational Fluid Dynamics (CFD) research into how urban morphology affects ventilation in cities. However, studies are scattered, with varying parameter definitions, limiting their application in architectural and urban design. This article aims to review and assess the relevance of geometric parameters studied in aerodynamics field to urban planning and architectural design in polish conditions. By reviewing previous publications on morphological parameters in wind studies, it evaluates their recognition and potential for their implementation in urban and architectural design in Polish conditions. Comparisons are made between these parameters and those commonly used in architectural and urban theory and practices in Poland. Results reveal minimal convergence, incorporating other parameters requires interdisciplinary research and significant planning procedure changes. This highlights the need for detailed interdisciplinary research and substantial planning changes to fully integrate CFD results into architectural and urban design practice in Poland.